Extension specialists’ vision of marketing problems for agricultural crops and how to confront them in light of the state’s approach to achieving food security in some governorates - Arab Republic of Egypt - Shalaby, Mohamed Youssef; Bekheit, Ahmed Anter; Sakr, Islam Hassan; Mekawy, Hanan Fathi; El-Assar, Tayseer Mumtaz (Journal of agricultural, environmental and veterinary sciences, 2023)
This study aimed to identify the most important marketing problems which are facing the farmers according to its relative importance from the point of view of extension specialists which are working in the field of agricultural marketing, in addition to recognize the most important causes of these problems, and their suggested solutions which have the possibility of reducing the marketing problems severity from the respondents’ point view. Finally, putting up proposal visualization for a marketing model can be contributing in reducing the severity of these problems and to improve the recent Egyptian marketing situation for the respondents in the research area. This research was conducted in seven Egyptian governorates as following: Qena, Sohag, Assiut, Beni Sueif, Minya, Beheira, and Kafr El-Sheikh, The research population represented all the extension specialists in these governorates, who were (125) respondents. The most important results were represented as the following: There are 25 marketing problems mentioned by the respondents, low prices and underestimating the rights of farmers as a result of the exploitation and greed of merchants and middlemen, then followed by the absence of the role of cooperative associations in the field of agricultural marketing, especially for small farmers, those two problems were mentioned at the forefront of problems. With regard to the most important reasons for these problems, they were as follows: The number of reasons mentioned by the respondents was (22) reasons, and in the first order of these reasons was the increasing in the cultivated area and the supply of some crops as a result of the lack of organization of the production process due to the improvement of prices in the previous season. Regarding the proposed solutions, which amounted to 26 solutions, the most important solutions were: the need to follow the policy of pre-contracting for the sale of agricultural crops and to set controls that guarantee the rights of the contracting parties, and under the supervision of a neutral party such as agricultural extension. Proposed marketing in cooperation with the formation of marketing links, and agricultural extension as a link between traders and small farmers to protect them from the greed of traders.